Effects of MCF2L2, ADIPOQ and SOX2 genetic polymorphisms on the development of nephropathy in type 1 Diabetes Mellitus - Gu Harvest F; Brismar Kerstin; Efendic Suad; Zhang Dongying (BMC, 2010)
Abstract Background MCF2L2, ADIPOQ and SOX2 genes are located in chromosome 3q26-27, which is linked to diabetic nephropathy (DN). ADIPOQ and SOX2 genetic polymorphisms are found to be associated with DN. In the present study, we first investigated the association between MCF2L2 and DN, and then evaluated effects of these three genes on the development of DN. Methods A total of 1177 type 1 diabetes patients with and without DN from the GoKinD study were genotyped with TaqMan allelic discrimination. All subjects were of European descent. Results Leu359Ile T/G variant in the MCF2L2 gene was found to be associated with DN in female subjects (P = 0.017, OR = 0.701, 95%CI 0.524-0.938) but not in males. The GG genotype carriers among female patients with DN had tendency decreased creatinine and cystatin levels compared to the carriers with either TT or TG genotypes. This polymorphism MCF2L2-rs7639705 together with SNPs of ADIPOQ-rs266729 and SOX2-rs11915160 had combined effects on decreased risk of DN in females (P = 0.001). Conclusion The present study provides evidence that MCF2L2, ADIPOQ and SOX2 genetic polymorphisms have effects on the resistance of DN in female T1D patients, and suggests that the linkage with DN in chromosome 3q may be explained by the cumulated genetic effects.